2016
DOI: 10.1093/mnras/stw1953
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for detecting the Rossiter–McLaughlin effect of Earth-like planets: the test case of TRAPPIST-1b and c

Abstract: The Rossiter-McLaughlin effect is the principal method of determining the skyprojected spin-orbit angle (β) of transiting planets. Taking the example of the recently discovered TRAPPIST-1 system, we explore how ultracool dwarfs facilitate the measurement of the spin-orbit angle for Earth-sized planets by creating an effect that can be an order of magnitude more ample than the Doppler reflex motion caused by the planet if the star is undergoing rapid rotation. In TRAPPIST-1's case we expect the Rossiter-McLaugh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…In parallel, large-aperture ground-based telescopes coupled to high-resolution spectrographs could be used to infer the properties of the TRAPPIST-1 system and the planetary atmospheres. Such observations could lead to (i) the detection of the Rossiter-McLaughlin effect (Rossiter 1924 ; McLaughlin 1924 ; Cloutier and Triaud 2016 ) to further constrain the orbital architecture of the system and confirm the 3.3 days rotation period of TRAPPIST-1, which is a crucial assumption in the stellar contamination model of Morris et al. 2018a .…”
Section: Future Prospectsmentioning
confidence: 93%
See 1 more Smart Citation
“…In parallel, large-aperture ground-based telescopes coupled to high-resolution spectrographs could be used to infer the properties of the TRAPPIST-1 system and the planetary atmospheres. Such observations could lead to (i) the detection of the Rossiter-McLaughlin effect (Rossiter 1924 ; McLaughlin 1924 ; Cloutier and Triaud 2016 ) to further constrain the orbital architecture of the system and confirm the 3.3 days rotation period of TRAPPIST-1, which is a crucial assumption in the stellar contamination model of Morris et al. 2018a .…”
Section: Future Prospectsmentioning
confidence: 93%
“…In parallel, large-aperture ground-based telescopes coupled to high-resolution spectrographs could be used to infer the properties of the TRAPPIST-1 system and the planetary atmospheres. Such observations could lead to (i) the detection of the Rossiter-McLaughlin effect (Rossiter 1924;McLaughlin 1924;Cloutier and Triaud 2016) to further constrain the orbital architecture of the system and confirm the 3.3 days rotation period of TRAPPIST-1, which is a crucial assumption in the stellar contamination model of Morris et al 2018a. Hirano et al (2020 have very recently made a first potential detection of the Rossiter-McLaughlin effect with the Subaru-IRD spectrograph and derived a projected rotation velocity of TRAPPIST-1 of 1.49 +0.36 −0.37 km s −1 , which corresponds to a maximum stellar rotation period of 3.97 +1.32 −0.77 days, in agreement with the 3.3 days rotation period from the K2 light curves.…”
Section: Future Prospectsmentioning
confidence: 99%
“…We note, though, that our result for v sin i s is lower than the value of 6 ± 2 km s −1 reported by Reiners & Basri (2010), which we believe was mistaken. In fact, the high value of v sin i s reported earlier made the prospect of RM observations appear easier than it was in reality; for instance, Cloutier & Triaud (2016) predicted an RM amplitude of 40 − 50 m s −1 based on this larger v sin i s . To make sure that our measurement of λ is not vulnerable to v sin i s , we fitted the RV data with v sin i s being fixed at 1.8 km s −1 .…”
Section: Modeling Of the Rm Effectmentioning
confidence: 95%
“…We ensured here the efficient calculation of well sampled MCMC chain, since the estimated mean acceptance fraction of ∼ 0.44 was found to be consistent within the ideal range of 0.2-0.5 (see Foreman-Mackey et al 2013;Cloutier & Triaud 2016;Stefansson et al 2017). To assess the convergence of MCMC chain, we estimated the integrated autocorrelation time of the chain averaged across parameters (Goodman & Weare 2010;Foreman-Mackey et al 2013) and found its value to be 2018).…”
Section: New Ephemerismentioning
confidence: 99%